PENERAPAN PELAKSANAAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) BPJS KESEHATAN PADA PASIEN HIPERTENSI DI PUSKESMAS SIPEA-PEA SORKAM BARAT - Dinda Sari Apriliani; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
Chronic disease is one of the main causes of death in Indonesia. According to data from the North Sumatra Provincial Health Office for 2019, the prevalence of high blood pressure in Central Tapanuli Regency is 97.71%. Identify the implementation of the Chronic Disease Management Program (Prolanis) in hypertension at the Sipea-Pea Public Health Center. This research is qualitative by using a case study strategy. The research subjects were 18 informants who were selected using a purposive technique. Data analysis was carried out based on inductive logic obtained from in-depth interviews. Qualitative data is presented in the form of narratives and tables. The coverage of prolanis program compliance can be seen from the contact rate indicator that has not been reached by the Sipea-pea Health Center with a contact rate ratio of 108 per mil and an indicator for the ratio of prolanis participants who routinely visit only up to the standard safe zone, namely 69 percent due to lack of socialization regarding prolanis. The health center limits prolanis participation because of doubts in controlling regular visits every month. The health center holds prolanis activities that are not routinely carried out, namely gymnastics and home visits. It is necessary to procure training to improve the skills of officers and update knowledge. Patient compliance needs to increase awareness by carrying out educational activities to the puskesmas area on a regular basis.